2011
DOI: 10.1089/cmb.2011.0126
|View full text |Cite
|
Sign up to set email alerts
|

Novel Definition and Algorithm for Chaining Fragments with Proportional Overlaps

Abstract: Abstract. Chaining fragments is a crucial step in genome alignment. Existing chaining algorithms compute a maximum weighted chain with no overlaps allowed between adjacent fragments. In practice, using local alignments as fragments, instead of MEMs, generates frequent overlaps between fragments, due to combinatorial reasons and biological factors, i.e. variable tandem repeat structures that differ in number of copies between genomic sequences. In this paper, in order to raise this limitation, we formulate a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Although it is not the ultimate genome aligner, we argue that in practice, YOC combines important advantages: Simplicity of the algorithm: only similarity detection and chaining are performed, which avoids including badly aligned regions. Simplicity of use: as the spaced seeds are already optimized for bacterial genomes, YOC only requires the tuning of two parameters: (i) the E-value threshold for YASS, the higher the better if the goal is to ensure high sensitivity regardless of the level of divergence, and (ii) the overlap ratio for the chaining algorithm even though, as shown in [ 35 ], OC results are highly robust with respect to this parameter. MGA, MAUVE, and ProgressiveMAUVE include additional parameters linked to the four phases strategy, for instance the lengths of the matches that are used in the first and the third phases (P1 and P3) are critical.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although it is not the ultimate genome aligner, we argue that in practice, YOC combines important advantages: Simplicity of the algorithm: only similarity detection and chaining are performed, which avoids including badly aligned regions. Simplicity of use: as the spaced seeds are already optimized for bacterial genomes, YOC only requires the tuning of two parameters: (i) the E-value threshold for YASS, the higher the better if the goal is to ensure high sensitivity regardless of the level of divergence, and (ii) the overlap ratio for the chaining algorithm even though, as shown in [ 35 ], OC results are highly robust with respect to this parameter. MGA, MAUVE, and ProgressiveMAUVE include additional parameters linked to the four phases strategy, for instance the lengths of the matches that are used in the first and the third phases (P1 and P3) are critical.…”
Section: Discussionmentioning
confidence: 99%
“…In [ 35 ], we argued that the difficulty of using local alignments is that the chances that two adjacent fragments overlap are much higher than with short matches. At that point, we observed that such overlaps are commonly due to randomness, to methodological reasons during the fragment computation phase, or to biological phenomena, like tandem repeats.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations